A Content Analysis of Communication in Agrarian Conflict Resolution between the Indramayu Farmers' Union and Perum Perhutani - Ballian Siregar; Sumardjo Sumardjo; Sarwititi Sarwoprasodjo; Ninuk Purnaningsih (Ikatan Sarjana Komunikasi Indonesia, 2023)
Agrarian conflicts in Indramayu between the Indramayu Farmers' Union (STI) and Perum Perhutani are complex issues that involve various parties and different interests related to agricultural land. This research aims to analyze conflict resolution using a communication approach. This study employs a constructive paradigm with a qualitative content analysis method. The research highlights critical strategies, including accurate understanding and effective information dissemination. An in-depth understanding of ownership rights, laws, and regulations is necessary for all parties. Information dissemination through various communication channels, such as open meetings, workshops, and social media, helps reduce misunderstandings and improve transparency. They were second, creating a space for dialogue and active participation of involved parties. Dialogue spaces allow parties to speak openly, listen to perspectives, and seek solutions by involving STI, Perum Perhutani, the government, law enforcement agencies, NGOs, academics, and the community. The creation of dialogue spaces should be inclusive. Furthermore, negotiation and mediation approaches help reach a middle ground. Negotiation allows parties to discuss differences and find mutually beneficial agreements. Mediation, involving a neutral third party, facilitates dialogue and finds solutions acceptable to all parties. This approach focuses on collaboration for sustainable resolution. Finally, a holistic approach involves legal clarification, community empowerment, livelihood diversification, and improved communication. Conflict resolution considers social, cultural, and economic aspects. A combination of conflict resolution strategies can address agrarian conflicts in Indramayu, leading to harmonious agricultural land management and promoting the parties' well-being.